A (des)articulação do ensino fundamental e a formação dos professores - Santos, Maurício Pastor; Gisi, Maria Lourdes [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2017)
This study intends to analyze the school routine and the pedagogical practices characteristic of inicial and final years of elementary school, considering the municipalization process that occurred in the state of Paraná in recent decades and the sharp increase in the rate of age-grade distortion and in the rate of grade failure in the 6th year, calculated by the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Inep). The focus is on the research on the disarticulation that exists within the same stage of basic education, contemplating the viewpoint of education professionals who work directly with these students. The data were collected by means of interviews with 20 teachers from state schools in the city of Curitiba who teach in the 6th grade; documental analysis on the current legislation; data released by Inep/Ministério da Educação (MEC); and studies about this subject. The analysis unveiled the need for collaborative initiatives that promote the expansion of the joint discussion between teachers who work in each of those phases, given that the present difficulties in this transition, identified by the research, became evident not only in the state schools but also in municipal ones that offer the two phases of elementary school. Therefore, it is inevitable to consider the difficulties related to the curricular structure and pedagogical practices, which are different in both phases and which present indications associated with learning difficulties.

Esse estudo busca analisar o cotidiano escolar e as práticas pedagógicas características dos anos iniciais e finais do ensino fundamental, considerando o processo de municipalização ocorrido no estado do Paraná nas últimas décadas e a acentuada elevação da taxa de distorção idade-série e de reprovação no 6º ano, apuradas pelo Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Inep). O foco é a investigação sobre a desarticulação que existe dentro de uma mesma etapa da educação básica, contemplando o ponto de vista dos profissionais da educação que atuam diretamente com esses estudantes. Os dados foram obtidos mediante entrevista semiestruturada com 20 professores de escolas estaduais do município de Curitiba que atuam no 6º ano; análise documental relativa à legislação vigente; dados divulgados pelo Inep/Ministério da Educação (MEC); e estudos existentes sobre a temática. As análises apontam para a necessidade de ações colaborativas que proporcionem a ampliação do debate conjunto entre professores que atuam numa e noutra fase, uma vez que as dificuldades presentes nessa transição, identificadas pela pesquisa, evidenciam-se tanto nas escolas da rede estadual quanto nas escolas da rede municipal de ensino que ofertam as duas fases do ensino fundamental. É preciso, assim, considerar as dificuldades relacionadas à estrutura curricular e à prática pedagógica que são distintas nas duas fases e que apresentam indícios associados às dificuldades de aprendizagem.
The (dis)articulation of elementary school and the teacher training
Keywords: municipalization; elementary school; teacher training.; municipalização; ensino fundamental; formação de professores.